Efektifitas Penghimpunan Dana Zakat (Studi Badan Amil Zakat Nasional Kota Bengkulu Tahun 2022) - Tri Wiwin; Supardi Supardi; Katra Pramadeka (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2023)
The aim of this research is to determine the effectiveness of collecting zakat funds at BAZNAS Bengkulu City and to find out how effective BAZNAS Bengkulu City's zakat fund collection is. This type of research is a mixed method which is a combination of qualitative and quantitative approaches by calculating a number of ratios related to the collection of zakat funds in 2022 and using descriptive aims to describe the conditions of effectiveness of the collection of BAZNAS zakat funds in Bengkulu City. From the results of this research it can be concluded that: The effectiveness of BAZNAS City Bengkulu zakat fund collection is effective as seen from the effectiveness indicators of Duncan's theory, while from the calculation results of the formula 20 ratio measurement, zakat fund collection is quite effective with a result of 5.18% with an interpretation of 2% < R < 5% so there needs to be an evaluation of the collection of zakat funds so that it is effective and has a wide impact, especially for the people of Bengkulu City.